Importance Of Length-Length And Length-Weight Relations In Crayfish - Harlıoğlu, Ayşe Gül (Fırat University, 2019)
The measurement of individual’s body weight and length is a fundamental procedure in the scientific study of a species. Regression equations of the relationships between length-length and length-weight in crayfish are used to compare populations in terms of condition, growth and development, sexual maturity and populations in different regions. On the other hand, the most important factors affecting the meat yield in freshwater crayfish include ecological characteristics, genetic structure and catching time. In addition, in the determination of meat yield content, the relations between length-length and length-weight are commonly used. In this study, the importance of length-length and length-weight relationships in freshwater crayfish is explained in detail.